Implementation of Hygienic Solar Drying Technology to Increase Sales Turnover of Melinjo Chips MSMEs - Fatah, Kemas Muhammat Abdul; Wibowo, Heri; Luthfi, Muhammad; Dimyati, Arzaq Guruh (Institut Teknologi Nasional, Bandung, 2026)
The constraints of MSMEs emping melinjo are on the supply side, where the increase in demand for melinjo chips cannot be matched by production capacity. Production capacity is highly dependent on the drying process. The drying process of emping melinjo is highly dependent on the season. In addition to requiring a relatively long time, emping melinjo is easily contaminated by microbes, making it unhygienic. Related to the constraints faced by MSMEs, the drying process must be improved so that the drying process is fast and hygienic by implementing a hygienic dryer. This PKM activity is divided into several stages, starting with the survey and literature study stage, ending with the evaluation stage. This dryer is constructed knockdown with 5 mm transparent clear glass material, the door is made of a vertical lift door, the walls of the dryer are insulated with glass wool and equipped with a turbine ventilator for better air circulation. Based on the evaluation results, this technology is able to speed up the drying process so that MSME turnover increases by up to 79% and workers' wages increase by 66.7%, resulting in better product quality and of course hygienic.